1995
DOI: 10.1007/bf02246194
|View full text |Cite
|
Sign up to set email alerts
|

Phencyclidine injections into the dorsal hippocampus disrupt long- but not short-term memory within a spatial learning task

Abstract: Since the hippocampus is likely to be a major site of phencyclidine (PCP) action, the effects of various doses of PCP (1.8, 18 or 36 nM) as well as 3.6 nM MK-801 or saline injected directly into the dentate gyrus of the hippocampus was tested for acquisition of a spatial navigation task (dry land version of a water maze) using a paradigm that assesses short term memory based on learning within a day and long term memory based on learning between days. Results indicated that relative to saline or 1.8 nM PCP inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Almost identical findings have been reported that posttraining intraperitoneal (ϩ)MK-801 administration or intrahippocampal injection of AP5 and phencyclidine, NMDA receptor antagonists, showed no impairment of the retention of shortterm memory and working memory. 20,21,8) In the present study, it was found that (ϩ)MK-801 potentiated the effects of muscimol on the retention of spatial working memory. Similar results have also been reported; for instance, Aversano et al 22) reported that (ϩ)MK-801 potentiated the effect of ethanol on memory consolidation in the …”
Section: Discussionsupporting
confidence: 59%
“…Almost identical findings have been reported that posttraining intraperitoneal (ϩ)MK-801 administration or intrahippocampal injection of AP5 and phencyclidine, NMDA receptor antagonists, showed no impairment of the retention of shortterm memory and working memory. 20,21,8) In the present study, it was found that (ϩ)MK-801 potentiated the effects of muscimol on the retention of spatial working memory. Similar results have also been reported; for instance, Aversano et al 22) reported that (ϩ)MK-801 potentiated the effect of ethanol on memory consolidation in the …”
Section: Discussionsupporting
confidence: 59%
“…Accordingly, maternal rats exhibit enhanced foraging/spatial ability in an 8-arm radial maze, and in an analog of the Morris Water Maze (viz. the dry land maze; Kesner & Dakis, 1995) in which they learn the location of a baited food well (Bodensteiner, Cain, Ray, & Hamula, 2005;Gatewood et al, 2005;Kinsley et al, 1999;Love et al, 2005;Pawluski, Walker, & Galea, 2006). Enhanced (and accurate) processing of the social surround, weighing threat against maternal aims is another ancillary maternal behavior central to successful parenting; postpartum rats performed better than NULL subjects in social learning tasks that were independent of pup or maternal cues (Fleming, Kuchera, Lee, & Winocur, 1994).…”
Section: Maternal Behavior and Neural Plasticitymentioning
confidence: 96%
“…In this study, the animals were behaviorally tested at six, twelve, eighteen, and twenty-four months of age on a spatial learning task, which required them to remember the location of a baited food well in the dry land maze (DLM; a Morris water maze analog; Kesner and Dakis 1995). Beginning at 12 months of age, and continuing until 24 months, the animals underwent additional testing (on a so-called reversal task), which required that they ''un-learn'' the original contingency, and learn a new location for the food reward, thereby assessing the flexibility of their learning.…”
Section: Evidence For Reproductive Experiential Mediation Of Nervous mentioning
confidence: 99%